2000
DOI: 10.1530/eje.0.1430197
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of proinflammatory cytokines in Graves' disease: effect of treatment, thyroid function, ophthalmopathy and cigarette smoking

Abstract: Objective: In the present study we have measured the concentrations of interleukin-6 (IL-6), soluble IL-6 receptor (sIL-6R), tumor necrosis factor-a (TNF-a), interleukin-1b (IL-1b) and IL-1 receptor antagonist (IL-1Ra) in the serum of patients with Graves' disease (GD). By multivariate analysis, we have evaluated the effect of antithyroid treatment, thyroid function, the presence or absence of active thyroid-associated ophthalmopathy (TAO), the patient's smoking habits and the relation to circulating anti-thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
68
3
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 35 publications
12
68
3
5
Order By: Relevance
“…Except in one study (22), no effect of thyroid status on serum levels of TNF-a has been demonstrated (23)(24)(25)(26). Only a few studies on serum PAI-1 levels have been presented showing an increased level in hyperthyroidism (27) and a decreased level in severe hypothyroidism (28).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Except in one study (22), no effect of thyroid status on serum levels of TNF-a has been demonstrated (23)(24)(25)(26). Only a few studies on serum PAI-1 levels have been presented showing an increased level in hyperthyroidism (27) and a decreased level in severe hypothyroidism (28).…”
Section: Discussionmentioning
confidence: 93%
“…However, a prolonged effect of thyroid hormone excess still present after eight or more weeks of anti-thyroid treatment cannot be excluded. Serum concentrations of IL-6 after treatment for Graves' disease have been shown to be both unaltered (23,30) or declined (22,24). Moreover, increased serum levels of IL-6 have also been found in non-autoimmune thyrotoxicosis (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…Wahrenberg et al (24) have reported that adipose tissues from these individuals release several-fold higher levels of IL-6 than do similar tissues from control subjects. Circulating IL-6 levels have also been found to be elevated in Graves' disease (17)(18)(19)(20)(21)(22). Moreover, treatment of thyrotoxicosis fails to normalize these levels, suggesting strongly that they are a consequence of the underlying autoimmune process.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, IL-6 has generated considerable interest because it has been implicated in human autoimmune diseases and multiple myeloma (15,16). IL-6 and soluble IL-6R, like several other important cytokines, have been found to be elevated in patients with Graves' disease (17)(18)(19) and those with TAO (20 -23). IL-6 protein can be detected in s.c. fat in these patients (24).…”
Section: Il-1␤ Induces Il-6 Expression In Human Orbital Fibroblastsmentioning
confidence: 99%
“…First, the hyperthyroid state increases levels of proinflammatory cytokines. [26][27][28] Transforming growth factor-␤ is associated with the inhibition of surfactant protein expression in human lung cell cultures. 8 Therefore, in the hyperthyroid state, the increase in transforming growth factor-␤ levels causes a lack of adequate surfactant production and release.…”
Section: Thyroid Hormone and Lung Developmentmentioning
confidence: 99%